2022
DOI: 10.4103/jfmpc.jfmpc_2451_21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hematological parameters in pulmonary tuberculosis patients

Abstract: Introduction: Tuberculosis (TB) is the most common infectious disease caused by mycobacterium tuberculosis. Apart from the lungs, tuberculosis also affects the bone marrow. There are significant hematological abnormalities that occur in association with tuberculosis. So we can use these hematological parameters as a marker for the diagnosis, prognosis, and response to therapy. Aims: To evaluate the hematological parameters in pulmonary tuberculosis patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
6
1
1
Order By: Relevance
“…12 In India, Shah et al reported a proportion of males at 64% among studied subjects. 13 These previous findings altogether agree with our documented finding on male predominance in this study. However, our study is in contrast to a study by Abdelkareem et al in Egypt, where the number of female PTB participants were higher compared to males.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…12 In India, Shah et al reported a proportion of males at 64% among studied subjects. 13 These previous findings altogether agree with our documented finding on male predominance in this study. However, our study is in contrast to a study by Abdelkareem et al in Egypt, where the number of female PTB participants were higher compared to males.…”
Section: Discussionsupporting
confidence: 93%
“…In India, Shah et al reported normocytic normochromic anemia in 40% of PTB patients while Abdelkareem et al in Egypt reported 37% for the same. 13,14 The proportion of microcytic hypochromic anemia in this study was significantly lower when compared to proportions reported by Abdelkareem et al in Egypt at 55% and Shafee et al in Pakistan at 52%. 14,21 Conversely, Ongwae et al reported a proportion that was substantially lower for microcytic hypochromic at 20% in Kenya.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Improving results of treatment, life quality and survival of patients all rely on hematological marker-based infection surveillance and control like tuberculosis. These haematological results can aid in attracting the attention of specialists and primary care support staff quickly, which is crucial for the early diagnosis of alterations in TB patients [6]. Despite gradual declines in both incidence and mortality rates, There are an estimated 10 million new cases of tuberculosis (TB) per year, leading to an estimated 1.2 million fatalities [7].…”
Section: Introductionmentioning
confidence: 99%